Zeolite synthesis from Brazilian coal fly ash for removal of Zn2+ and Cd2+ from water - Izidoro, J.; Fungaro, D.; Wang, Shaobin (Trans Tech Publications, 2011)
A Brazilian fly ash sample (CM1) was used to synthesize zeolites by hydrothermal treatment. Products and raw materials were characterized in terms of real density (Helium Pycnometry), specific surface area (BET method), morphological analysis (SEM), chemical composition (XRF) and mineralogical composition (XRD). The zeolites (ZM1) from fly ash were used for metal ion removal from water. Results indicated that hydroxy-sodalite zeolite could be synthesized from fly ash sample. The zeolite presented higher specific surface area and lower SiO2/Al2O3 ratio than the ash precursor. The adsorption showed that cadmium is more preferentially adsorbed on ZM1 than zinc. The adsorption equilibrium time for both Zn2+ and Cd2+ was 20 hours in a batch process. The adsorption isotherms were better fitted by the Langmuir model and the highest percentages of removal using ZM1 were obtained at pH 6 and 5 and doses of 15 and 18 g L-1 for Zn 2+ and Cd2+ , respectively. Thermodynamic studies indicated that adsorption of Zn2+ and Cd2+ by ZM1 was a spontaneous, endothermic process and presented an increase of disorder at the interface solid/solution.